The valproate prescription pattern for female mental healthcare users of reproductive age - Phumla S. Gasa; Andrew Tomita; Vidette Juby; Saeeda Paruk (South African Journal of Psychiatry, 2024)
Background: Sodium valproate (valproate) that is used both as an anti-epileptic and a mood stabiliser is teratogenic in pregnancy. A Dear Health Care Professional Letter (DHCPL) issued in December 2015 recommended the avoidance of sodium valproate prescription in women of childbearing age (WOCBA) and pregnant women.